Ibn Al-Baraq Al-Wadi Ashi (529 AH _ T 596 AH) His life and what remains of his poetry - صفاء عبد الله برهان, أ.م .د. (lark, 2020)
This research is an academic endeavor made by the researcher to introduce the poet Ibn al-Buraq al-Wadi Ashi al-Andalus, who was one of the most prominent poets of Andalusia in the sixth century AH, and who had an important position in his time and Egypt, he mentioned it was still among most scholars of Andalusian literature. Because of the lack of news that were transmitted to us, verses, verses from his poetry in the Hijri century and the seventh, but the return of time came to the vast majority of that great heritageWhat prompted the researcher to collect the fragments of what was left of his poetry written in the pages of Andalusian and Moroccan sources, and then organize it in this poetry collection, so that the research was divided into two parts, the first identifying his journey in this life, and the other documenting the remainder of his poetry.Which represents a first step. You are waiting for some days to find manuscript sources, to be discovered here or there; To complete the image of Ibn al-Buraq the poet.Key words: (Ibn al-Buraq, Wadi Ash, al-Ra'aini's choices, Andalusian poetry
Keywords: Ibn al-Buraq, Wadi Ash, al-Ra'aini's choices, Andalusian poetry